Adab dan Akhlak Sebagai Fondasi Pendidikan: Sosisalisasi Program Kerja KKN di Sekolah Dasar Negeri 11 Patamuan - Saputra, Syahnan; Sabaniah, Nofetriani; Idris, Saufi Zahra; Prinata, Fadhil Surya; Ningsih, Sri Wahyuni; Annanda, Yefri; Andrianto, Andrianto; Amris, Firda Khairati; Ariani, Farida (Institut Agama Islam Sumatera Barat, 2024)
In the era of increasingly rapid globalization, moral and ethical challenges are becoming increasingly important, especially in Indonesia, where the development of information and communication technology has had a negative impact on children's moral and ethical values. Character education in the national curriculum is often less than optimal, focusing more on cognitive aspects compared to emotional aspects. This article explains how the Community Service Program (KKN) can be a solution to the lack of moral education in elementary schools. This program involves students as facilitators and role models in the socialization of manners and ethics through educational methods, mentoring, and the use of audiovisual media. The results of the socialization show that the contextual approach and integration of simple technology have a positive impact on the formation of students' personalities with noble and honest morals. Program It also emphasizes the need to integrate theory and practice to achieve optimal results in character education